Clinicopathological features and incidence of micrometastases in the bone marrow and peritoneum in advanced carcinoma of stomach in Indian patients - Samraj, Anita; Mathew, George; Nair, Aravindan (International Surgery Journal, 2017)
Background: Gastric cancer is associated with high mortality. The current five-year survival rate is less than 20%. Preventing the development of gastric cancer or finding it at the earliest possible stage is a far more cost-effective way of dealing with this tumour than the treatment of patients with advanced local regional or metastatic disease. The introduction of immunocytological methods that using monoclonal antibodies, sensitive enough to identify even single tumour cells can now be used to detect secondary metastatic sites. The objective of this study was to evaluate the patients with advanced gastric carcinoma using various factors such as presenting symptoms, predisposing risk factors and evidence of micro metastases by analysis of bone marrow and peritoneal cytology and also to identify any specific risk factors in a group of patients and if there were evidence of early micro metastases in these patients. Methods: Around 30 patients with histologically and endoscopically diagnosed gastric carcinoma, admitted in CMCH, surgery unit I was included in the study. All patients with gastric carcinoma had bone marrow smear and biopsy prior to surgery. Results: In all 30 patients, the periperal bone marrow smears and the bone marrow biopsy was negative for malignant cells. Only 1 patient had evidence of atypical cells on examination of the peritoneal fluid for cytology. 14 patients had less than 3 lymph nodes positive. In 7 patients, more than 3 lymph nodes were positive. 23.3% of the patients had H.Pylori associated gastritis. Conclusions: Smoking and alcohol were found to be significant risk factor. There was a significant association of H.pylori infection in the group. There was only one patient detected to have malignant cells in the peritoneal washings analyzed cytologically. In this study, no significant incidence of micro metastases in the bone marrow or elevated CEA levels in the peritoneal fluid were found.